Pengaruh Woolwich Massage Terhadap Pengeluaran ASI Pada Ibu Post Partum - Qomariah Khusnul Khotimah; Rifzul Maulina (Journal of Innovative and Creativity, 2025)
Postpartum mothers often face challenges in producing sufficient breast milk for their infants, with factors such as stress, muscle tension, and lack of breast care affecting lactation. Woolwich Massage, a technique involving gentle massage around the breast area, is believed to stimulate blood circulation, improve circulation, and provide relaxation, thereby enhancing milk production. This study aims to examine the effect of Woolwich Massage on breast milk production in postpartum mothers. The research utilized an experimental pre-test and post-test design with two groups: an intervention group that received regular Woolwich Massage and a control group that did not receive the intervention. The results showed that the intervention group had a significant increase in breast milk production, with an average increase of 40 ml per session over two weeks, compared to the control group, which showed a smaller increase of 10 ml per session. Statistical analysis using the Wilcoxon Signed Ranks Test revealed significant differences in both groups (p < 0.05). These findings indicate that Woolwich Massage is effective in stimulating blood circulation around the breast and helps increase milk production. Additionally, the relaxation effects of the massage aid in reducing stress, which further supports milk production. This study suggests that Woolwich Massage can be considered an effective non-pharmacological therapy for enhancing breast milk production in postpartum mothers.